2020
DOI: 10.1101/2020.02.18.946335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin D receptor protects against dysbiosis and tumorigenesis via the JAK/STAT pathway in intestine

Abstract: 26Background: Vitamin D exerts regulatory roles via vitamin D receptor (VDR) in mucosal 27 immunity, host defense, and inflammation involving host factors and microbiome. Human Vdr 28 gene variation shapes the microbiome and VDR deletion leads to dysbiosis. Low VDR expression 29 and diminished vitamin D/VDR signaling are observed in colon cancer. Nevertheless, how 30 intestinal epithelial VDR is involved in tumorigenesis through gut microbiota remains unknown. 31We hypothesized that intestinal VDR protects mic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Results from a large cohort suggest that higher level of VDR expression is associated with longer survival after surgical resection in patients with colorectal cancer. 6 This clinical evidence is supported by studies from Zhang et al 7 to elucidate a previously unrecognized mechanism through which the intestinal epithelial VDR regulates the homeostasis of the gut microbiome for preventing development of inflammation-associated colorectal cancer. Through a series of elegant in vivo and in vitro studies using human samples and mouse models of colorectal cancer, they report that the absence of VDR in intestinal epithelial cells results in shifting the gut bacterial profile toward that with high risk for colorectal cancer.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…Results from a large cohort suggest that higher level of VDR expression is associated with longer survival after surgical resection in patients with colorectal cancer. 6 This clinical evidence is supported by studies from Zhang et al 7 to elucidate a previously unrecognized mechanism through which the intestinal epithelial VDR regulates the homeostasis of the gut microbiome for preventing development of inflammation-associated colorectal cancer. Through a series of elegant in vivo and in vitro studies using human samples and mouse models of colorectal cancer, they report that the absence of VDR in intestinal epithelial cells results in shifting the gut bacterial profile toward that with high risk for colorectal cancer.…”
mentioning
confidence: 85%
“…Through a series of elegant in vivo and in vitro studies using human samples and mouse models of colorectal cancer, they report that the absence of VDR in intestinal epithelial cells results in shifting the gut bacterial profile toward that with high risk for colorectal cancer. 7 They further demonstrate that dysbiosis in mice with VDR deletion in intestinal epithelial cells promotes tumorigenesis through stimulating antiinflammatory JAK/STAT3 signaling in intestinal epithelial cells. 7 It has been reported that alterations in the composition, distribution, or metabolism of the gut microbiota may produce an environment in the colon that promotes inflammation, dysplasia, and cancer.…”
mentioning
confidence: 94%
See 2 more Smart Citations